Molecular epidemiology of antimicrobial resistant microorganisms in the 21th century: a review of the literature: MDR molecular epidemiology in the 21th century - Genovese, Cristina; La Fauci, Vincenza; D'Amato, Smeralda; Squeri, Andrea; Anzalone, Carmelina; Costa, Gaetano Bruno; Fedele, Francesco; Squeri, Raffaele (Acta Biomedica Atenei Parmensis, 2020)
Healthcare-associated infections (HAIs) are the most frequent and severe complication acquired in healthcare settings with high impact in terms of morbidity, mortality and costs. Many bacteria could be implicated in these infections, but, expecially multidrug resistance bacteria could play an important role. Many microbial typing technologies have been developed until to the the bacterial whole-genome sequencing and the choice of a molecular typing method therefore will depend on the skill level and resources of the laboratory and the aim and scale of the investigation. In several studies the molecular investigation of pathogens involved in HAIs was performed with many microorganisms identified as causative agents such as Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Clostridium difficile, Acinetobacter spp., Enterobacter spp., Enterococcus spp., Staphylococcus aureus and several more minor species. Here, we will describe the most and least frequently reported clonal complex, sequence types and ribotypes with their worldwide geographic distribution for the most important species involved in HAIs.